Prevalence of anti‐severe acute respiratory syndrome coronavirus 2 antibodies in cats in Germany and other European countries in the early phase of the coronavirus disease‐19 pandemic. (2nd March 2022) - Adler, Julia Maria; Weber, Corinna; Wernike, Kerstin; Michelitsch, Anna; Friedrich, Karin; Trimpert, Jakob; Beer, Martin; Kohn, Barbara; Osterrieder, Klaus; Müller, Elisabeth
Abstract: During the first months of the coronavirus disease (COVID‐19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), cases of human‐to‐cat transmission were reported. Seroconversion was shown in cats infected under experimental and natural conditions. This large‐scale survey of 1, 005 serum samples was conducted to investigate anti‐SARS‐CoV‐2 antibody prevalence in domestic cats during the first 7 months of the pandemic in Germany and other European countries. In addition, we compared the sensitivity and specificity of two multispecies SARS‐CoV‐2 antibody enzyme‐linked immunosorbent assays (ELISA). Results were confirmed by using an indirect immunofluorescence test (iIFT) and a surrogate virus neutralization test (sVNT). Sera that were highly positive for feline coronavirus (FCoV) antibodies ( n = 103) were included to correct for cross‐reactivity of the tests used. Our results showed an overall SARS‐CoV‐2 seropositivity of 1.9% ( n = 19) in a receptor‐binding domain (RBD)‐based ELISA, additional 0.8% ( n = 8) were giving inconclusive results. In contrast, a nucleocapsid‐based ELISA revealed 0.5% ( n = 5) positive and 0.2% ( n = 2) inconclusive results. While the iIFT and sVNT confirmed 100% of positive and 50%–57.1% of the doubtful results as determined in the RBD ELISA, the nucleocapsid‐based assay showed a high discrepancy and only one of the five positive results could be confirmed. The results indicate significant deficits of the nucleocapsid‐based ELISA with respect to sensitivity and specificity. Due to a significantly higher rate (5.8%) of positive results in the group of highly FCoV antibody‐positive samples, cross‐reactivity of the FCoV‐ELISA with SARS‐CoV‐2 antibodies cannot be excluded. Furthermore, we investigated the impact of direct contact of domestic cats ( n = 23) to SARS‐CoV‐2 positive owners. Considering one inconclusive result, which got confirmed by iIFT, this exposure did not lead to a significantly higher prevalence (4.4%; p = .358) among tested subjects. Overall, we conclude that cats are a negligible entity with respect to virus transmission in Europe.